Zatsnuy Ju. A. Сoncerning intervariant borrowings as a source of enreching the colloquial lexicon and fraseology in the modern Еnglish language - Zatsnuy Ju. A. (Philological Treatises, 2020)
The article introduces the issue of “internal borrowings” as major source of enriching the vicabulary of colloquial English. Some aspects of contacts between the national varietis of English are also touched.